The use of synthetic agonists of quorum sensing N- acyl homoserine lactone pathway improves the bioleaching ability in Acidithiobacillus and Pseudomonas bacteria - Caicedo, Juan Carlos; Villamizar, Sonia [UNESP]; Orlandoni, Giampaolo (PeerJ, 2022)
Metal solubilization from discarded electrical material and electronic devices (e-waste) using the bioleaching capabilities of bacterial cells is highly effective. However, gaps in understanding about the microbiological processes involved in the bioleaching reaction leads to less efficient metal solubilization in large-scale e-waste processing. In this study, bacterial species belonging to the genera Acidithiobacillus and Pseudomonas were used to leach copper and gold from discarded printed circuit boards (PCB). Through modulation of the cell-to-cell communication system in these bacteria, phenotypic traits directly involved in the bioleaching reaction were regulated in order to improve the metal solubilization. Addition of the long chain synthetic autoinducer molecule N-acyl homoserine lactone (AHL) of the quorum sensing pathway to the bioleaching reaction resulted in a significant enhancement of metal extraction from PCB. Factors such as: cell attachment to PCB, biofilm formation and hydrogen cyanide (HCN) production were regulated by the quorum sensing system and could be directly related to the improvement of metal bioleaching. Bioleaching reactions using bacterial quorum sensing modulation could represent a valuable tool in overcoming limitations at the industrial level imposed by microbiological traits that lead to inefficient metal bioleaching from e-waste.
Keywords: Auto-inducer; Biofilm; Bioleaching; Cell attachment; Hydrogen cyanide